Chemical elements in the aragonitic and calcitic microstructural groups of shell of the oysterCrassostrea virginica: A proton probe study - Carriker, M. R.; Swann, C. P.; Prezant, R. S.; Counts, C. L. (Marine Biology, 1991)
We report the results of a study with proton-induced X-ray emissions (PIXE) of the distribution and concentration of 15 chemical elements (Na to Sr in periodic chart) in four microstructural and two mineralogical regions of shell of rapidly growing adult oysters [Crassostrea virginica (Gmelin)]. Hatchery-raised oysters were grown in Broadkill Estuary, Delaware, USA, for 16 wk in summer 1978. Their valve edges were filed as a marker, and the oysters were replaced in the estuary, where they grew rapidly. Shell deposited after marking had a normal microstructure and mineralogy after a narrow zone of disturbance. After 17 d oysters were sacrificed, and different mineralogical and microstructural regions of valves of three oysters, and parts of valves of two oysters, were analyzed for the elements Na to Sr. Quadrats (2.5 × 0.45 mm) included three calcitic groups (prismatic, foliated, chalky) and one aragonitic (myostracal) microstructural group; four quadrats were on the exterior and five on the interior of right and left valves. Inhalant and exhalant margins of valves and ground right and left valves of one oyster were also analyzed. Elemental chemistry of different regions of shell varied among the three microstructural groups within the single calcitic polymorph, between aragonitic and calcitic regions, and between exhalant and inhalant margins of the valves. Elements were most concentrated in the prismatic region of the right valve. Element concentrations were similar in ground right and left valves, except for higher levels of Si, Fe, and Zn in the right valve (corresponding to their high contents in prismatic shell) and of Cl in the left valve (reflecting high concentration in chalky shell, abundant in this valve). Na, Mg, Cl, Cr, Cu, Zn and Br were more concentrated in prismatic than in foliated shell. Chalky shell contained higher concentrations of Na than did prismatic shell, and high concentrations (but lower than in prismatic shell) of Mg, Cl, Ti, Mn, Fe, Zn and Br. Element concentration in myostracum was approximately the same as, or lower than, in foliated shell, except for Sr, which was higher than that in any other shell group. In the right valve most elements were concentrated in inhalant margins, and on the left valve, in exhalant margins. With increased weathering of the exterior surface of prismatic shell, Mg, Si, and Mn increased in concentration and Na, Al, Cl, Ti, Cr, Fe, Br, and Sr decreased.
31 citations (Crossref) [2023-10-31]
Keywords: Chemical Element; Crassostrea Virginica; Elemental Chemistry; Exterior Surface; PIXE; dept.aa

A freshwater bioprobe: Periostracum of the Asian Clam, Corbicula fluminea (Müller) combined with laser microprobe mass spectrometer - Hutchinson, P. J.; Rollins, H.; Sharkey, A. G.; Prezant, R. S.; Kim, Y.; Hercules, D. M. (Environmental Pollution (Barking, Essex: 1987), 1993)
A freshwater bioprobe, combining the Asiatic Clam, Corbicula fluminea (Müller) and the laser microprobe mass spectrometer (LAMMA), can determine anthropogenic chemical contamination of freshwater systems. Laser generated mass spectra from the periostracal layers of clams contaminated with either a salt, potassium bromide, or an aromatic compound, phenol, produce distinctive mass spectral signatures that are different from uncontaminated clams. Uncontaminated clams have characteristic signatures with distinctive spectral peaks less than m/z 41; while exposed clams have many strong peaks well above this m/z. This freshwater bioprobe, using LAMMA to analyze the surface of clams, can be used as a screening tool for monitoring the water-treatment systems, for determining the source of contaminated baseflow and return flow discharge to streams, and for monitoring the water chemistry of a body of water. This system exploits the facility of using the shell instead of soft tissue with the LAMMA and has potential to detect anthropogenically-derived chemical stress.
3 citations (Crossref) [2023-10-31]
Keywords: dept.aa

Detection of xenophobic response in the periostracum of the bivalve,Corbicula fluminea, through laser-induced mass spectrometry - Hutchinson, Peter J.; Rollins, Harold B.; Prezant, Robert S. (Archives of Environmental Contamination and Toxicology, 1993)
Aqueous-phased xenobiotic contaminant exposure can biochemically modify newly generated periostracum of the Asian freshwater bivalve,Corbicula fluminea. Laser-induced desorption of partially polymerized periostracum produces spectra distinguishable from mass spectral images generated from uncontaminated periostracum. Organic xenobiotic contamination putatively impedes full polymerization of the periostracin protein. The detection of the effects of pollution on periostracum by the laser microprobe mass analyzer constitutes a novel bioprobe for the definitive but qualified detection of xenobiotic contamination.
2 citations (Crossref) [2023-10-31]
Keywords: Bivalve; Mass Spectrometry; Polymerization; Waste Water; Water Pollution; dept.aa